554 Utilization of Pediatric Sleep Questionnaire to Screen for Obstructive Sleep Apnea in a Difficult-to-treat Asthma Cohort. (3rd May 2021) - Lin, Nancy; Hantragool, Sumalee; Huang, Guixia; Hossain, Md Monir; McDowell, Karen; Guilbert, Theresa; Kercsmar, Carolyn; Simakajornboon, Narong
Abstract: Introduction: Early detection and management of obstructive sleep apnea(OSA) could improve asthma control in children with difficult-to-treat(DTT) asthma. The purpose of this study was to assess the effectiveness of the pediatric sleep questionnaire(PSQ) to screen for OSA in children with DTT asthma, and to compare clinical characteristics between those with positive and negative PSQ scores. Methods: A prospective study of 81 children with DTT asthma was completed from 2015–2017. The PSQ, Epworth sleepiness scale(ESS), Pediatric Quality of Life(PQL), and the academic performance questionnaires(APQ) were administered during clinic visits. Polysomnography(PSG) was recommended for PSQ score>0.33. Medical records were reviewed for asthma clinical characteristics. The cohort was separated into positive(PSQ>0.33) and negative PSQ score(PSQ≤0.33) groups for analysis. Results: The mean age of the cohort was 11.3±4.5 years and the mean body mass index was 22±7.6 kg/m2. Sixty-two percent were male and 68% were African-American. Forty-nine(53%) subjects had positive PSQ (0.5[0.4 – 0.7]). The positive group had higher ESS score (10.5[8 – 13] vs. 6[2 – 8], p<0.0001) and lower total PQL score (58.7[47.8–72.8] vs. 79.4[70.7 – 87], p<0.0001) than the negative group. There was no difference between APQ scores(p=0.07). The positive group had lower asthma control test(ACT) scores than the negative group (17.5[15 – 20.5] vs. 21[19 – 22], p<0.0001). Furthermore, the positive group was more likely to have gastroesophageal reflux (OR: 3.97, 95%CI: 1.7 to 9.1, p=0.0018). Twenty-nine(59%) subjects in the positive group had subsequent PSG, and 17(58.6%) subjects were diagnosed with OSA (14 mild OSA, 1 moderate OSA, 2 severe OSA). The mean obstructive index in the positive group was 3±5.5 events/hour. There was 1 subject with central apnea and alveolar hypoventilation. Of the 17 subjects with OSA, all received treatment with nasal steroids, 3 were treated with non-invasive positive pressure ventilation, and 4 had surgical intervention. Conclusion: Children with DTT asthma who have positive PSQ have higher degree of daytime sleepiness, lower quality of life and worse asthma control. The positive group was more likely to have GERD, which may suggest a relationship between nighttime asthma symptoms and OSA. Further studies are needed to evaluate the effects of OSA treatment on asthma control. Support (if any):